GOOD VS. EVIL: THEMES IN ’THE LORD OF THE RINGS’ TRILOGY - Umida Abdushukurova (Journal of new century innovations, 2024)
J.R.R. Tolkien's "The Lord of the Rings" trilogy stands as a timeless testament to the enduring struggle between good and evil. In this abstract, we delve into the multifaceted exploration of this theme within Tolkien's richly crafted world of Middle-earth. Through a comprehensive analysis, we examine the portrayal of good and evil through characters such as Frodo, Gandalf, and Sauron, exploring their motivations, actions, and moral complexities. Additionally, we explore the symbolism of the One Ring as a manifestation of corruption and power, as well as the moral dilemmas faced by characters throughout their quest. Furthermore, we investigate the influence of Tolkien's own experiences and beliefs on the moral themes of the story, including his Catholic faith and literary inspirations. By considering the legacy and impact of "The Lord of the Rings," we recognize its profound resonance with readers and its enduring influence on the portrayal of good vs. evil in fantasy literature. Through this exploration, we gain a deeper understanding of the eternal battle that lies at the heart of Tolkien's masterpiece.